2015
DOI: 10.1371/journal.pone.0141901
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Left Atrial Appendage in Human Hearts

Abstract: Atrial fibrillation increases the risk of thrombus formation. It is commonly responsible for cerebral stroke whereas less frequently for pulmonary embolism. The aim of the study was to describe the morphology of the left atrial appendage in the human heart with respect to sex, age and weight. Macroscopic examination was carried out on 100 left appendages taken from the hearts of the patients aged 18–77, both sexes. All hearts preserved in 4% water solution of formaldehyde carried neither marks of coronary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 25 publications
(24 reference statements)
0
15
0
2
Order By: Relevance
“…Veinot et al observed a series of autopsies comprising 500 normal human hearts (age range: 0–100 years) and found that the distribution of number of LAA lobes was 2 (54%), 3 (23%), 1 (20%), and 4 (3%). Kamiński et al confirmed considerable morphological differences in LAA. On the basis of 220 LAA casts examinations, Ernst et al observed variability of LAA.…”
Section: Discussionmentioning
confidence: 99%
“…Veinot et al observed a series of autopsies comprising 500 normal human hearts (age range: 0–100 years) and found that the distribution of number of LAA lobes was 2 (54%), 3 (23%), 1 (20%), and 4 (3%). Kamiński et al confirmed considerable morphological differences in LAA. On the basis of 220 LAA casts examinations, Ernst et al observed variability of LAA.…”
Section: Discussionmentioning
confidence: 99%
“…The first stage of the research was to construct right ventricle models using a silicone molding compound (Xiameter 4250 S Green). The applied technique has already been used in the case of modeling the heart's appendages [10]. Before modeling, the hearts were thoroughly rinsed with cold water to remove blood clots from the inside.…”
Section: Methodsmentioning
confidence: 99%
“…С точки зрения патогенеза формирования процесса тромбообразования достаточно сложно представить, что эпизод вдФП вызвал тромбоэмболию, привед-шую к нарушению мозгового кровотока с развитием обширного повреждения головного мозга со столь выраженным неврологическим дефицитом. Воз-можно, последующие исследования должны быть связаны, в том числе, с изучением особенностей гео-метрии ушка левого предсердия, его анатомо-мор-фологических особенностей, приводящих в столь коротком временном периоде к тромбообразованию [18]. Безусловно данные вопросы требуют прове-дения специально спланированных исследований у пациентов с вдФП.…”
Section: таблица 2 факторы риска смерти для больных с фп перенесшихunclassified